Glass Mountain - Harpa Hrund Pálsdóttir 1984- (2018)
Glass is all around us, in our buildings, computers, soda bottles, jewellery and kitchenware but most of us don’t give it a second thought, don’t realise or think about where it comes from and where it ends up. It has been intertwined with human history for thousands of years but somewhere along the way we lost sight of the wonder it invoked in people in earlier times. This thesis takes a hard look at glass; its nature and chemistry, its industrial history in Iceland, import, recycling and reusing glass in modern day Iceland. The research of this thesis can be divided in three: Written sources, on site visits and written conversations (email) with key figures in the relevant industries. Written sources included, among others, relevant books about glass making, Icelandic industrial history, reports on specific matters along with various articles on related subjects such as geology, chemistry and world history. Printed and online sources were used equally. A significant part of the research utilised Tímarit.is where old newspaper articles and advertisement gave a valuable insight in the history of glass in Iceland. Visits were made to two glass factories in Iceland, Íspan and Samverk, and artist Sigrún Einarsdóttir and conversations had with representatives of Ölgerðin and Endurvinnslan. The history of glass making in Iceland is a story of ambitious ideas and failure that often evokes questions that are hard to answer in hindsight. Making glass from Icelandic material is indeed possible as shown by early, positive research. The materials needed can be found locally but production is hindered by the size of our population, ease of import and the understandable demand for profitability. However the opportunities in recycling, small batch artisan production and repairs are plentiful and attainable.